GRAPHIC RESULTS OF DETERMINATION OF CAR MOVEMENT ON THE SORTING SLOPE OF THE SLIDE WITH A FAIR WIND - Jabbarov Shukhrat Botirovich; Saidivaliev Shukhrat Umarkhojaevich; Abdullaev Bakhrom Aktamovich; Yuldoshov Rustam Madamin ugli; Zhumabekov Bobur Sheralievich (Scientific Trends, 2022)
In the article, the results of tabular data of previously performed studies of the movement of a wagon along the descent part of the marshalling yard - from its top to the calculated point under the influence of a tailwind of small magnitude are presented in a convenient for plotting graphical dependencies. For the first time, graphical dependences of the acceleration, travel time and rolling speed of the car on the length of the descent part of the hill have been constructed.
Keywords: railway, station, hump, wagon, tailwind, presentation of research results in graphical form, analysis of research results